Military Customs and Traditions / Militêre gewoontes en tradisies. - Militaria, Editorial Team (Scientia Militaria - South African Journal of Military Studies, 2012)
Tattoo According to Boatner, the word probably originated among British troops in Holland during the Thirty Years War (1618 - 1648) or during the wars of King William III during the 1690's.The word is derived from the Dutch 'tap' (tap or faucet) and 'toe' (to or off). When the time came for the soldiers to leave the taverns and return to their billets, the Officer of the Day, with a sergeant and drummer beat his way through the streets. This was the signal for the Dutch tavern keepers to 'Doe den tap toe' or turn off the taps.